Comparative Study Between Pulse Therapy with Oral Itraconazole Versus Continuous Oral Terbinafine Therapy for Treatment of Onychomycosis - Mahboob Ali, Muhammad Adeel Siddiqui, Majid Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to evaluate the efficacy of onychomycosis treatment using pulses of oral itraconazole vs continuous dosing with oral terbinafine. Study Design: Randomized Control Trial Place and Duration of Study: Department of Dermatology, Combined Military Hospital, Abbottabad from 01 Mar, 2022 to 01 Aug, 2022. Methodology: A total of 100 patients were included in this research study who were divided in two groups through blocked randomization and were enrolled through nonprobability consecutive sampling technique. Data was collected, entered, and analyzed using SPSS Version 23.0. Results: In oral itraconazole (pulse therapy) group, 43 (86.0%) patients showed effective results while in oral terbinafine (continuous therapy) group, 32 (64.0%) showed effective results. P Value = 0.011. Conclusion: This study demonstrated that oral itraconazole (pulse therapy) is significantly superior to oral terbinafine (continuous therapy) group in the treatment of treatment of onychomycosis. Keywords: Onychomycosis, Fungal Infection, Pulsed Therapy, Continuous Itraconazole Therapy.